1987
DOI: 10.1128/mcb.7.4.1338
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Saccharomyces cerevisiae equivalent of ribosomal protein S6 has no detectable effect on growth.

Abstract: The phosphorylation of mammalian ribosomal protein S6 is affected by a variety of agents, including growth factors and tumor promoters, as well as by expressed oncogenes. Its potential role in the regulation of protein synthesis has been the object of much study. We have developed strains of Saccharomyces cerevisiae in which the phosphorylatable serines of the equivalent ribosomal protein (S10) were converted to alanines by site-directed mutagenesis. The S10 of such cells is not phosphorylated. Comparison of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…These differences are consistent with the fact that in yeast r-protein mRNAs lack 5ЈTOP sequences and phosphorylation of ribosomal protein S6 is not essential for normal cell growth (Johnson and Warner, 1987), features that are required for the observed translational regulation in mammalian cells. On the other hand, it has not been reported whether rapamycin affects r-protein gene transcription in mammalian cells.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These differences are consistent with the fact that in yeast r-protein mRNAs lack 5ЈTOP sequences and phosphorylation of ribosomal protein S6 is not essential for normal cell growth (Johnson and Warner, 1987), features that are required for the observed translational regulation in mammalian cells. On the other hand, it has not been reported whether rapamycin affects r-protein gene transcription in mammalian cells.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, although yeast ribosomal protein S6 is normally phosphorylated in a manner that parallels the growth rate of the cell, no obvious growth defect results when the phosphorylation sites are mutated (Johnson and Warner, 1987). Thus the question arises as to what role TOR signaling plays in ribosome synthesis in yeast.…”
Section: Introductionmentioning
confidence: 99%
“…We also indicated that phosphorylation of both the serine residues is dispensable for cell viability in fission yeast. Similarly, in budding yeast, phosphorylation of the conserved serine residues is not necessary for cell survival and protein synthesis (Johnson and Warner, 1987). In the case of mouse, phosphorylation of S6 is also dispensable for cell viability, whereas phosphorylation of the ribosomal protein is involved in cell size and glucose homeostasis (Ruvinsky et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, this enzyme/substrate pair of PRMT3/rpS2 is evocative of the S6 kinase/rpS6 pairing. Both enzyme substrate pairs have been conserved over an extended evolutionary period and are found from yeast to man (4,5,21,22). The phosphorylation of rpS6 occurs in response to numerous growth stimulatory agents and temporally correlates with the initiation of protein synthesis (23).…”
Section: Prmt3-deficient Embryos Are Small-at Weaning Prmt3mentioning
confidence: 99%